The endoparasite Perkinsus olseni affecting the Mediterranean mussels (Mytilus galloprovincialis) in the Italian and Spanish waters: A new possible threat for mussel aquaculture and wild animal population - Carella, Francesca; Fernandez Tejedor, Margarita; Villari, Grazia; Andree, Karl Blyth; De Vico, Gionata (Frontiers in Marine Science, 2023)
Dinoflagellates belonging to the Perkinsus genus are OIE (World Organization for animal Health)-listed pathogens extremely virulent for clams and oysters in many marine ecosystems throughout the world. During the monitoring activities of the Mediterranean mussel (Mytilus galloprovincialis) in Campania region (Italy), the presence of typical trophozoites of Perkinsus sp. was observed in mussels from farms and natural banks. Simultaneously, following mussel mortality in the Spanish waters of Catalonia, histopathological studies revealed the presence of the same parasite. Although perkinsosis is an endemic disease in clams in Italy (with prevalence from 40 to 80%), there are no reports to date of its presence in Mediterranean mussels and of the effect on this species. For this study, histopathology, Ray’s Fluid Thioglycollate Medium (RFTM), and molecular diagnostics with conventional Polimerase Chain Reaction (PCR) and qPCR were performed. In samples from Italy, histopathology in the mussel from one farm revealed a prevalence of 26% in February 2019, 40% in February 2020, 16% in November 2020, and 23% in April 2021. In a natural bank, Perkinsus was also detected in May 2020 but in lower prevalence. In Spain, in July 2020, the presence of the parasite was 20% in one site and 10% in a second site and related to animal mortality. In both areas, Perkinsus sp. elicited multiple inflammatory capsules of different size or infiltrates at the level of the digestive gland and gonad. Molecular diagnostics of the Internal Transcriber Spacer (ITS) region of the rDNA (ITS1, 5.8S, and ITS2) showed a 97% similarity of P. olseni from Italy with samples from New Zealand, Australia, and Uruguay and in bivalves such as Pitar rostrata, Astrovenus sp., and Haliotis sp., whereas in Spain the identity was 99% samples from South Korean venerids such as Anadara granosa. Phylogenetic analysis group together P. olseni from Italian and Spanish mussels but place them distant from other P. olseni described in the clams from Europe (Italy, France, and Spain). Direct impact of transboundary animal diseases in aquaculture constitutes a serious consequence for export living animals and their products, as well for international trade. This compromises food security, also causing a high socioeconomic impact on aquaculture exporting nations. P. olseni is a generalist pathogen able to infect different bivalve species, possibly passing from clams to oysters and mussels. Recognized international organizations should take this into account in the view of possible cross-infection. Other studies are needed to define pathogen virulence in this species.